Răspuns :
[tex] \frac{2}{23} \times \frac{3}{5} - \frac{2}{5} \times \frac{3}{46} [/tex]
[tex] = \frac{2}{5} ( \frac{3}{23} - \frac{3}{46} )[/tex]
[tex] =\frac{2}{5} ( \frac{6}{46} - \frac{3}{46} )[/tex]
[tex] =\frac{2}{5} \times \frac{3}{46} [/tex]
[tex] = \frac{6}{230} [/tex]
[tex] = \frac{3}{115} [/tex]
[tex] = \frac{2}{5} ( \frac{3}{23} - \frac{3}{46} )[/tex]
[tex] =\frac{2}{5} ( \frac{6}{46} - \frac{3}{46} )[/tex]
[tex] =\frac{2}{5} \times \frac{3}{46} [/tex]
[tex] = \frac{6}{230} [/tex]
[tex] = \frac{3}{115} [/tex]